An Autopsy Case of a 5-Year-Old Child with Acute Pancreatitis Caused by Eosinophilic Granulomatosis with Polyangiitis-like Necrotizing Vasculitis - Haruna Yagi; Seishiro Takahashi; Tetsuo Kibe; Kenji Shirai; Isao Kosugi; Hideya Kawasaki; Shiori Meguro; Toshihide Iwashita; Hiroshi Ogawa (Case Reports in Rheumatology)
In children, acute pancreatitis has been reported in IgA vasculitis, Kawasaki disease, systemic lupus erythematosus-associated vasculitis, and juvenile dermatomyositis-associated vasculitis. However, its frequency in these vasculitides has been shown to be low. In other childhood-onset vasculitides, acute pancreatitis is seldom reported. The patient was a 5-year-old Japanese boy who suddenly presented with gastrointestinal (GI) bleeding. Therapy with antiulcer drugs successfully stopped bleeding, but subsequently, high fever, leukocytosis, and hypoxia appeared. He died 12 days after he presented with GI bleeding. An autopsy unexpectedly revealed that necrotizing vasculitis with marked eosinophilic and histiocytic infiltration of the pancreas led to acute pancreatitis, and gastric ulcer with eosinophilic infiltration was shown to be the origin of GI bleeding. In addition, eosinophilic infiltration was found in the small intestine, lungs, and bone marrow. Necrotizing vasculitis with eosinophilic and histiocytic infiltration of the pancreas, eosinophilic infiltration of the airway wall, and eosinophilic gastroenteritis with gastric ulcer were histologically confirmed, suggesting that the present case may be an early stage of eosinophilic granulomatosis with polyangiitis- (EGPA-) like vasculitis. To our knowledge, this might be the first reported case of EGPA-like vasculitis presenting with acute pancreatitis in a child.